Effect of nickel on the comparative performance of inverse fluidized bed and continuously stirred tank reactors for biogenic sulphur-driven autotrophic denitrification. (1st December 2020) - Namburath, Maneesh; Papirio, Stefano; Moscariello, Carlo; Di Costanzo, Nicola; Pirozzi, Francesco; Alappat, Babu J.; Sreekrishnan, T.R.
Abstract: The comparative performance of an inverse fluidized bed reactor (IFBR) having high density polyethylene beads as carrier materials for biofilm formation and a continuous stirred tank reactor (CSTR), both maintaining autotrophic denitrification using biogenic sulphur (ADBIOS) in the absence and presence of nickel (Ni 2+ ), was studied. The reactors were compared in terms of NO3 − -N and NO2 − -N removal and SO4 2- -S production throughout the study. A simulated wastewater with an inlet NO3 − -N concentration of 225 mg/L and a decreasing concentration of biogenic sulphur (bio-S) from 1.5 to 0.375 g/L was used. Both reactors were operated at a hydraulic retention time (HRT) of 48 h for 140 days and at an HRT of 42 h for the following 68 days. A more efficient ADBIOS was observed in the CSTR than IFBR throughout the study due to a better mixing of the feed wastewater in the bulk liquid and a higher availability of bio-S to the suspended cells. The NO3 − -N removal efficiency in the IFBR decreased by approximately 41% when the feed bio-S was reduced to 0.375 g/L, while it remained unaffected in the CSTR. Conversely, the presence of Ni 2+ did not significantly affect NO3 − -N removal in both reactors even at a feed Ni 2+ concentration of 120 mg/L. The highest NO3 − -N removal rates achieved were 86 and 108 mg NO3 − -N/(L·day) in the IFBR and CSTR, respectively, in the presence of 120 mg/L of feed Ni 2+ at an HRT of 42 h. Batch studies conducted with acclimatized biomass showed that the continuous-flow operation mode in both reactors played a major role in helping the autotrophic denitrifiers to tolerate Ni 2+ toxicity. Graphical abstract: Image 1 Highlights: Autotrophic denitrification with biogenic S (ADBIOS) was studied in IFBR and CSTR. The highest removal rates were 86 and 108 mg NO3 − -N/(L·day) in IFBR and CSTR. Ni 2+ was fed to both reactors on day 91 and gradually increased up to 120 mg/L. Continuous-flow mode played a crucial role in the tolerance of denitrifiers to Ni 2+ . The ADBIOS performance in IFBR was not affected even at 120 mg/L of Ni 2+ .